The Compressive Strength of Geopolymer Mortar with the Alkali Silica Ratio of 2.5 - Revanska Harbyansyah; Ade Sri Wahyuni; Agustin Gunawan; Mukhlis Islam; Yuzuar Afrizal (Universitas Bengkulu, 2026)
The cement industry accounts for approximately 7% of global CO₂ emissions, driving the development of environmentally friendly alternatives such as geopolymer concrete. Geopolymers are formed from silica (SiO₂) and alumina (Al₂O₃) rich materials that are reacted with an alkaline solution. This study utilized fly ash from Teluk Sepang Power Plant in Bengkulu to prepare geopolymer mortar. Seventy-two 5×5×5 cm cubic samples were prepared with 2,5 ratio of sodium silicate to sodium hydroxide (SS/SH) and 8M NaOH. The curing process was carried out at ±80°C for 24 hours. The results showed that calcination of fly ash significantly increased the initial compressive strength. On day 7, the compressive strength reached 92.9% of the 28-day age, with a final value of 38.1 MPa. Mortar with calcined fly ash showed a compressive strength 97.7% higher on day 7 compared to normal fly ash, and 11.5% higher on day 28. Additionally, the setting time of the mortar was reduced by 46.8% with calcination. The pattern of compressive strength development from calcined fly ash tended to be stable from the beginning, unlike normal fly ash. Keywords: Geopolymer Mortar, Calcination, Fly Ash, Compressive Strength